OPEN CIRRUS: A GLOBAL CLOUD COMPUTING TESTBED. - Avetisyan, Arutyun I.; Campbell, Roy; Gupta, Indranil; Heath, Michael T.; Ko, Steven Y.; Ganger, Gregory R.; Kozuch, Michael A.; O'Hallaron, David; Kunze, Marcel; Kwan, Thomas T.; Lai, Kevin; Lyons, Martha; et al. (Computer (00189162), 2010)
The article focuses on the cloud computing testbed called Open Cirrus. The main goals of Open Cirrus are presented, which include fostering of systems-level research in cloud computing, encouraging new cloud computing applications research, and offering a collection of experimental data. It examines the architectural choices for the design of the testbed which include systems versus application-only research, federated versus unified sites, and data-center focus versus centralized homogeneous infrastructure.